Direct interaction analysis of microRNA-351-5p and nuclear scaffold lamin B1 mRNA by the cell-free in vitro mRNA/miRNA binding evaluation system. (2nd June 2020) - Sato, Akira; Ogino, Yoko; Shimotsuma, Akira; Hiramoto, Akiko; Kim, Hye-Sook; Wataya, Yusuke
Abstract: We previously demonstrated that miR-351-5p regulates nuclear scaffold lamin B1 expression and mediates the anticancer floxuridine-induced necrosis shift to apoptosis in mammalian tumor cells. Notably, it is unknown whether lamin B1 mRNA is a direct target of miR-351-5p. Here, we show that miR-351-5p interacts with a lamin B1 mRNA partial sequence by using the cell-free in vitro miRNA and mRNA binding evaluation system. In addition, the interaction of miR-351-5p/lamin B1 mRNA was suppressed by an miR-351-5p inhibitor. Our findings are important in exploring the functions of miRNAs in cellular processes, including cell death.